Studi Kelayakan Sarana Prasarana Rumah Susun Dok IX di Kota Jayapura: Studi Kasus : Kelurahan Tanjung Ria, Distrik Jayapura Utara Kota Jayapura - Vaan M Heremba; Deasy Widyastomo; Irja Tobawan Simbiak (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to assess the feasibility of facilities and infrastructure at the Dok IX Flats (Rumah Susun) located in Tanjung Ria Sub-district, North Jayapura District, Jayapura City, based on the Indonesian National Standard (SNI) 03-1733-2004, as well as residents’ perceptions. The research uses a mixed methods approach, combining quantitative and qualitative methods. Data were collected through field observations and questionnaires distributed to 43 respondents using the Likert scale. The results show that, in general, the housing complex is considered feasible, with an average score of 70 or 76.1%. Facilities such as education, health, worship, green open space, road access, and drainage are considered adequate. However, inconsistencies were found in the disaster mitigation system. Although categorized as